Improvement and evaluation for algebraic fault attacks on PRESENT - Jing HUANG; Xin-jie ZHAO; Fan ZHANG; Shi-ze GUO; Ping ZHOU; Hao CHEN; Jian YANG (Tongxin xuebao)
An enhanced algebraic fault analysis on PRESENT was proposed.Algebraic cryptanalysis was introduced to build the algebraic equations for both the target cipher and faults.The equation set of PRESENT was built reversely in order to accelerate the solving speed.An algorithm of estimating the reduced key entropy for given amount of fault injec-tions was proposed,which can evaluate the resistance of PRESENT against fault attacks under different fault models.Fi-nally,extensive glitch-based fault attacks were conducted on an 8-bit smart card PRESENT implemented on a smart card.The best results show that only one fault injection was required for the key recovery,this is the best result of fault attacks on PRESENT in terms of the data complexity.